1989
DOI: 10.1016/0014-5793(89)80692-1
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of the human nucleolin cDNA

Abstract: A cDNA containing the entire coding region for human nucleolin has been isolated from a 1 gtl0 human retinal library using a bovine cDNA probe. The cDNA hybridized to a transcript of 3000 bases from fast-dividing cells, as well as terminally differentiated tissues of several species. Translation of the nucleotide sequence revealed a long open reading frame which predicts a 707 amino acid protein with several distinct domains. These include repeating elements, four conserved RNA-binding regions, a glycine-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 36 publications
3
87
0
Order By: Relevance
“…A preferred affinity for single-stranded nucleic acids has also been found for the RGG domains from hnRNP A1 (13), hnRNP U (14), and nucleolin (15). The RGG-box of nucleolin displays a ␤-spiral structure that binds single-stranded nucleic acids with an induced base unstacking effect (39), most likely with the consequence of duplex unwinding (40).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A preferred affinity for single-stranded nucleic acids has also been found for the RGG domains from hnRNP A1 (13), hnRNP U (14), and nucleolin (15). The RGG-box of nucleolin displays a ␤-spiral structure that binds single-stranded nucleic acids with an induced base unstacking effect (39), most likely with the consequence of duplex unwinding (40).…”
Section: Discussionmentioning
confidence: 96%
“…The carboxylterminal 100 amino acids of NDH II consist of a consecutive stretch of glycines that is regularly interrupted by either aromatic amino acids or arginine. Similar RGG-rich sequences (RGG-boxes) have been found as part of many nucleic acidbinding proteins, such as the heterogeneous nuclear ribonucleoproteins hnRNP A1 (13) and hnRNP U (14), nucleolin (15), yeast single-strand DNA-binding protein 1 (16), as well as of other proteins from the superfamily of DEX(D/H) helicases (17)(18)(19)(20)(21)(22)(23). Except hnRNP U, where the RGG-box is the only nucleic acid binding domain (14), RGG-boxes cooperate with other domains to achieve an increased affinity for nucleic acids.…”
mentioning
confidence: 99%
“…hnRNP, heterogenous nuclear ribonucleoprotein ; KH domain, a peptide motif identified originally in hnRNP-K; PCBP, poly(C)-binding protein; CS-RBD, consensus-sequence RNA-binding domain; RRM, RNA recognition motif; 2D, two-dimensional. fuss et al, 1993) and this motif was also found in RRM-motifcontaining proteins, including nucleolin (Srivastava et al, 1989). This motif consists of one or more RGG boxes, that are repetitions of an Arg-Gly-Gly sequence interspersed with other, often aromatic, amino acids and it has been shown to interact directly with RNA (Kiledijan and Dreyfuss, 1992;Ghisolfi et al, 1992).…”
Section: Hagen Denmarkmentioning
confidence: 96%
“…The in vitro GST-SH2D1A binding proteins p160, p130, and p115 were identified as ␣-coatomer (24), hnRNPU (25) or GAPII, and nucleolin C23 (26) or Eps15R (17), respectively. The association of FLAG-SH2D1A with Eps15R could not be detected with anti-Eps15R antibodies.…”
Section: Dok1mentioning
confidence: 99%